Public Transport Challenges on User Satisfaction in Cities: A Case of Dar es Salaam - Michael, Charles; Layaa, John (AGUSPATI Research Institute, 2025)
This study examined the challenges of public transport and how they affect passenger satisfaction in Dar es Salaam City. The main goal was to understand how the quality of transport infrastructure, social factors, and daily transport operations influence how satisfied commuters are. A quantitative research approach with an exploratory design was used. Out of 384 targeted participants, 315 valid responses were received, giving an 82% response rate. The results showed that the average ratings for transport infrastructure, social aspects, operational aspects, and satisfaction were around 2.85, meaning most passengers felt neutral about the quality of services. Correlation analysis found very weak and statistically insignificant links between the studied factors and user satisfaction. Similarly, regression results showed low explanatory power, with R² values between 1.3% and 3.0%. None of the studied factors had a significant impact on how satisfied users were. These findings suggest that user satisfaction in Dar es Salaam’s public transport is influenced by other unmeasured or personal experiences that go beyond service quality. The study adds to the discussion on urban transport by showing that traditional service factors do not always explain satisfaction levels in developing countries. It recommends that policymakers and transport authorities use more inclusive and feedback-based planning approaches that focus on passengers’ real experiences. The study also suggests further research on emotional and social aspects such as fairness, safety, and respect in service delivery, especially in fast-growing African cities with limited infrastructure.